Transdifferentiation of adipocytes to osteoblasts: potential for orthopaedic treatment - Lin, D.; Dass, Crispin (John Wiley & Sons Ltd., 2018)
Â© 2018 Royal Pharmaceutical Society Objectives: As both adipocytes and osteoblasts originate from the same pool of mesenchymal stem cells, increasing clinical evidence has emerged of the plasticity between the two lineages. For instance, the downregulation of osteoblast differentiation and upregulation of adipogenesis are common features of conditions such as multiple myeloma, obesity and drug-induced bone loss in diabetes mellitus. However, despite in-vitro and in-vivo observations of adipocyte transdifferentiation into osteoblasts, little is known of the underlying mechanisms. Key findings: This review summarises the current knowledge of this particular transdifferentiation process whereby the Wnt/Î²-catenin signalling pathway and Runx2 overexpression have been postulated to play a critical role. Summary: Furthermore, due to the possibility of a novel therapy in the treatment of bone conditions, a number of agents with the potential to induce adipo-to-osteoblast transdifferentiation have been investigated such as all-trans retinoic acid, bone morphogenetic protein-9 and vascular endothelial growth factor.